My Problem is, this given second order non-linear differential equation: $$yy^{\prime\prime}=2(y^{\prime})^{2}-2y^{\prime}$$

I am really stuck with second-order differential equations.

My Approach: i was given the advise to solve first $$y^{\prime}=p(y)$$ and to determine $p$ but i didn't managed to get it.

I thought this: $$yy^{\prime\prime}=2(y^{\prime})^{2}-2y^{\prime}$$ could lead to: $$2y^{\prime}=2(y^{\prime})^{2}-yy^{\prime\prime}$$ $$y^{\prime}=(y^{\prime})^{2}-\frac{yy^{\prime\prime}}{2}$$

But i don't get it and i can't solve the equation.

  • $\begingroup$ @TonyPiccolo: I think you mean $\dfrac{\tan\left(\sqrt{C_1} (x+C_2)\right)}{\sqrt{C_1}}$ $\endgroup$ – Robert Israel Jun 24 '13 at 11:33
  • $\begingroup$ $y''=\frac{dy'}{dx} = \frac{dy}{dx}\frac{dy'}{dy}$ $\endgroup$ – Empy2 Jun 24 '13 at 11:35
  • $\begingroup$ @Robert Israel: Yes, thank you. I removed the comment because I was not sure. $\endgroup$ – Tony Piccolo Jun 24 '13 at 16:11

ODE has trivial solution $y=0$.

Now we have to solve case $y\neq 0$:

After dividing equation with $y^3$: $$\frac{y y''-2y'^2}{y^3}=\frac{-2y'}{y^3},$$ we get $(\frac{y'}{y^2})'$ on the left side and $(\frac{1}{y^2})'$ on the right side. Therefore, $$\frac{y'}{y^2}=\frac{1}{y^2}+C,$$ $$y'=1+Cy^2,$$ $$\frac{dy}{1+Cy^2}=dx.$$ After integration, we have $$\frac{1}{\sqrt{C}}\tan^{-1}(\sqrt{C}y)=x+D.$$ Finally, $$\frac{1}{\sqrt{C}}\tan{(\sqrt{C}(x+D))}=y.$$


Hint: You can write your differential equation in the form $$ \dfrac{y''}{y' - 1} = 2 \dfrac{y'}{y} $$ and both sides can be integrated...

  • $\begingroup$ No, $\int 2 \dfrac{y'}{y}\ dx = 2 \ln y + C$. And similarly for $\int \dfrac{y''}{y'-1}\ dx$. $\endgroup$ – Robert Israel Jun 24 '13 at 14:47
  • $\begingroup$ oh okay. But $\int \dfrac{y''}{y'-1}\ dx=ln(y'-1)+C$... and this would result in $$ln(y'-1)+C=2 \ln y+C$$ ... right? $\endgroup$ – Toralf Westström Jun 24 '13 at 19:25
  • $\begingroup$ Right (of course, the two $C$'s are not necessarily equal). Now exponentiate to get rid of the logs. $\endgroup$ – Robert Israel Jun 24 '13 at 20:02
  • $\begingroup$ okay, should i get this in the end? $$y=\tan (x+C)$$ $\endgroup$ – Toralf Westström Jun 24 '13 at 20:11
  • 1
    $\begingroup$ $y' = 1 + A y^2$ is a separable differential equation. $\endgroup$ – Robert Israel Jun 26 '13 at 6:46

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.